KOMUNIKASI TWO-WAY SYMMETRIC DALAM MENJALIN HUBUNGAN PUBLIC RELATIONS DENGAN MEDIA (STUDI PADA HUMAS PEMERINTAH KABUPATEN GOWA) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
The media have a role in disseminating information. On the other hand, the media plays a role as a bridge to convey correct information to the public, besides that the media also plays a role in disseminating certain information for the benefit of certain parties. The development of mass media is very rapid, starting from television, radio, newspapers and so on which can be used in the current information age. Public relations is an organization or company must establish good relations with the media. In the future, the two parties must continue to work together, because that is the goal of both parties can be achieved, namely the publication obtained by the organization/company, while the media environment continues to face challenges with the growing information age so that quality coverage that can provide information to the public can be achieved. fulfilled. This is what is being done by the Public Relations of the Gowa Regency Government, namely establishing a relationship with the media through the application of two-way symmetric communication. Two-way symmetric communication, in brief, is an ideal communication model. Where aims to form a state of mutual understanding between the two parties concerned. The communication carried out is two-way communication effectively and in balance.